A Comparative Study of the Leadership Behavior of Freshman and Final Year Undergraduate Students - Musa, Mihriay (Asian Journal of Education and Training, 2020)
This study was conducted to examine the leadership levels of university students by comparing them according to various variables. In our research, both qualitative and quantitative methods were used with the scanning model. The universe of the study consisted of the freshman and final year undergraduate students studying at Akdeniz University in the 2019-20 academic year. A simple random sampling method was used to determine the study group. The research sample determined in this way was composed of 175 students studying in the first and last years of the Faculty of Sport Sciences, Teaching, Coaching, Management, and Recreation Departments, respectively. In this study, the Leadership Qualities Scale, which was developed by Cansoy and Turan (2016) and consists of 28 questions, was used. Kruskal Wallis H test and Mann-Whitney U tests, which are nonparametric, were used to analyze the data. The leadership level of the students was found to be high. A difference was determined in leadership sub-dimensions. To eliminate these differences; self-confidence levels of teaching, sports management, and recreation department students; the level of responsibility of the students of teaching, coaching and recreation departments; the reliability levels of male students and the persuasion skills of first-year students should be increased.